Darkness and Light in Evelyn Underhill - Wrigley-Carr, Robyn (Journal of spiritual formation & soul care, 2019)
Evelyn Underhill (1875–1941) was one of the most widely read writers in spirituality in the first half of the twentieth century. In addition to her nearly 40 books and hundreds of articles and reviews, Underhill wrote a significant number of letters of spiritual direction and led spiritual retreats in England in the 1920s and 1930s. Darkness and light are recurring themes in both Underhill’s letters of spiritual nurture and in the prayers that she wrote and selected for use when leading retreats. These two themes also operate as a lens for exploring Underhill’s own personal, spiritual journey. In this article, the themes of darkness and light are explored in Underhill’s spiritual journey, in her soul care of others, as revealed through her letters, and in her prayers for retreat leading. Underhill provides us with wisdom concerning soul care for people experiencing darkness. She shows us how to help them endure and trust God when the light is gone.